Criteria for acquiring refugee status and restrictions on enjoying it - Khaldoun Hashim Rasool Al Sharqi; Ali Mahmoud Shukr (Eximia, 2024)
Given that States enjoy sovereignty over their territory, they have the right to individually adapt the issue of whether an individual is entitled to refugee status or not, following a series of procedures to determine refugee status. The term “determining refugee status” means asking whether someone is a refugee or not. Given the vital importance of answering this question for the person concerned, the importance of the procedures followed to determine his status becomes apparent. Any error in diagnosing his status may put his freedom or life at risk. The competent authorities in the country of asylum must conduct a thorough examination to determine whether the asylum seeker meets the conditions or not. The United Nations High Commissioner for Refugees monitors the extent to which the country of asylum adheres to the internationally applicable standards in this field. It may also actively participate in the procedures for determining refugee status if the country’s internal legislation is devoid of procedures in this regard, and it decides whether the asylum seeker is entitled to enjoy refugee status or not based on its 1950 Statute.